Use of Tannin from Mangrove {Rhizophora Apiculata) for Improving Thickening and Settleability of Sludge - Yaakob, Mohamad Azmi (Universiti Teknologi PETRONAS, 2006)
Tannin has been useful to humankind ever since it was found for its special ability in tanning hides as well as its medication benefits. However, the use of tannin from mangrove (Rhizophora Apiculata) in wastewater treatment still absent since mangrove only perceived as source for charcoal manufacturing. This research utilized the mangrove waste from charcoal factories to extract tannin and later being used for feasibility study on improving sludge settleability. Several natural waste products such as limestones powder, mangrove barktannin and modified mangrove bark tannin were used in settling and thickening of sludge. This was compared with commercial coagulant such as alum. Dosages of the natural products were varied by jar test procedure and settleability of sludge of sludge was measured. The supernatant ofthe settling test will be tested on chemical oxygen demand (COD), pH, turbidity and total suspended solids (TSS). It was found that the results from the preliminary shown raw mangrove bark powder can act as coagulant and as competitive with a commercial coagulant. The best settling rate of alum as coagulant is 0.692 cm/min at dosage of 4500 mg/ L but raw mangrove powder has proved to get the best settling rate at 2.98 cm/min at dosage of 4000mg/L. As for limestones, the best settling rate is only 0.259 cm/min. In the second phase of the research, for alum, the settling rate for zero dosage was the best at 0.436 cm/min. Fortannin extract in the first trial, the best dosage in the test was 2400 mg/L of tannin with 4.833 cm/min. In the second trial of settling test using tannin extract, dosage of 2400 mg/L has the highest settling rate with 3.48 cm/ min and dosage of 180 mg/L has the lowest settling rate of 0.0833 cm/min. For modified tannin extract in first trial, the best dosage was 3600 mg/L with settling rate of 4.32 cm/min while in second trial the best settling rate was achieved at dosage of 2400 mg/L with settling rate of 1.75 cm/min. In COD removal, alum (1500 mg/L) has shown the best percentage removal by 98.3 percentfollowed by modifiedtannin at dosage 7200 mg/L with 84.5 percent removal. For tannin, it has achieved 76.7 percent of COD removal at settling rate of 1.29 cm/min. In conclusion, the results obtained were encouraging but further research will pave ways to explore this alternative coagulant, which should perform better and healthier than commercial coagulant without compromising the economic values. IV